2007
DOI: 10.1177/154405910708600413
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Vascular Canals in Human Mandible and Other Bones

Abstract: The human mandible is highly mineralized. We hypothesized that this is related to the local vascularity of the bone. This could not be examined directly, but, as a surrogate, intracortical vascular canal spaces of the human mandible were studied so that we could determine possible relationships with age, gender, location, dental status, and tissue mineralization. Canal numbers, area, and volume fraction were calculated from quantitative backscattered electron images of human mandibles aged 16-96 years. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
(11 reference statements)
1
17
0
1
Order By: Relevance
“…However, even in the case of ONJ the mandible appears to be more frequently affected, particularly in patients treated with antiresorptives for the treatment of osteoporosis [2, 48, 49]. The predilection of the mandible for osteonecrosis could be due to the decreased vascularity, thicker cortical borders and smaller percentage of trabecular bone [50, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…However, even in the case of ONJ the mandible appears to be more frequently affected, particularly in patients treated with antiresorptives for the treatment of osteoporosis [2, 48, 49]. The predilection of the mandible for osteonecrosis could be due to the decreased vascularity, thicker cortical borders and smaller percentage of trabecular bone [50, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…While the femur has been analyzed more than any other bone, Renders et al (2007) reported a vascular porosity of ~4% in the human mandibular condyle. In addition, Kingsmill et al (2007) measured the vascular porosity using backscattered SEM at several skeletal sites, finding the most porous cortex to be the femoral neck, which had a mean vascular porosity (also referred to as cortical porosity) of 16%. In the mandible, the porosity varied depending in the site studied (3 – 11%), the vascular porosity of the fourth lumbar vertebrae was ~5%, and the vascular porosity in the iliac crest was ~8% (Kingsmill et al 2007).…”
Section: Vascular and Lacunar-canalicular Porositiesmentioning
confidence: 99%
“…In addition, Kingsmill et al (2007) measured the vascular porosity using backscattered SEM at several skeletal sites, finding the most porous cortex to be the femoral neck, which had a mean vascular porosity (also referred to as cortical porosity) of 16%. In the mandible, the porosity varied depending in the site studied (3 – 11%), the vascular porosity of the fourth lumbar vertebrae was ~5%, and the vascular porosity in the iliac crest was ~8% (Kingsmill et al 2007). In mice, μCT and SR-μCT were used in studies by Martin-Badosa et al (2003) and Schneider et al (2007, 2009) in which the vascular porosity in the femur was found to be in the range of ~1 – 5%.…”
Section: Vascular and Lacunar-canalicular Porositiesmentioning
confidence: 99%
“…The fraction of bone remodeled per year defines a turnover rate which change with age . Structural differences between bones, mainly variations in the degree of vascularization, might be the key factor regulating the remodeling process . Highly mineralized bones such as mandible have slower remodeling and turnover rates than post‐cranial bones, thereby reflecting different periods of isotopic integration among distinct skeletal bones.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the remodeling time of the trabecular bone is five to ten times faster than that of the cortical bone . Structural differences between bones, such as differences in the density, in the degree of mineralization and mainly variations in the degree of vascularization, may be the key factors regulating this process …”
mentioning
confidence: 99%